Una paz insostenible: abusos y embrollos discursivos en el uso del término “sostenible” aplicado a la idea de desarrollo (2020)
As suggested by its title, this paper deals with the idea of sustainable development and its lack of concreteness. Such a lack of concreteness is due to the verbose use given to the expression “sustainable”, which in turn has been favored by the fact that its content is originally non-specific and, therefore, useless to avoid the evils of developmentalism and its effects on society. Hence the proliferation of approaches which, since they are not radical criticisms, are also not capable of revealing themselves as alternatives to official arguments, due to a lack of attention to the fundamental assumptions that constitute them, as we will show from a critical analysis of the discourse of the original sources on the subject (mainly resolutions of the General Assembly and other United Nations documents), before focusing our attention on matters that are less speculative and more committed to direct actions of respect and care for people and their circumstances as preconditions for harmony.